Molecular Phylogenetic Analysis of Paracoccidioides Species Complex Present in Paracoccidioidomycosis Patient Tissue Samples - de Oliveira, Luciana Bonome Zeminian [UNESP]; Della Coletta, Amanda Manoel [UNESP]; Gardizani, Taiane Priscila [UNESP]; Garces, Hans Garcia [UNESP]; Bagagli, Eduardo [UNESP]; Trilles, Luciana; Barrozo, Ligia Vizeu; Marques, Sílvio de Alencar [UNESP]; Faveri, Julio De [UNESP]; Dias-Melicio, Luciane Alarcão [UNESP] (MDPI, 2023)
Paracoccidioidomycosis (PCM) is the main and most prevalent systemic mycosis in Latin America, that until recently, it was believed to be caused only by Paracoccidioides brasiliensis (P. brasiliensis). In 2006, researchers described three cryptic species: S1, PS2, PS3, and later, another one, PS4. In 2009, Paracoccidioides lutzii (Pb01-like) was described, and in 2017, a new nomenclature was proposed for the different agents: P. brasiliensis (S1), P. americana (PS2), P. restrepiensis (PS3), and P. venezuelensis (PS4). These species are not uniformly distributed throughout Latin America and, knowing that more than one cryptic species could coexist in some regions, we aimed to identify those species in patients’ biopsy samples for a better understanding of the distribution and occurrence of these recently described species in Botucatu region. The Hospital of Medical School of Botucatu—UNESP, which is a PCM study pole, is located in São Paulo State mid-west region and is classified as a PCM endemic area. Genotyping analyses of clinical specimens from these patients that have been diagnosed and treated in our Hospital could favor a possible correlation between genetic groups and mycological and clinical characteristics. For this, molecular techniques to differentiate Paracoccidioides species in these biopsies, such as DNA extraction, PCR, and sequencing of three target genes (ITS, CHS2, and ARF) were conducted. All the sequences were analyzed at BLAST to testify the presence of P. brasiliensis. The phylogenetic trees were constructed using Mega 7.0 software and showed that 100% of our positive samples were from S1 cryptic species, therefore P. brasiliensis. This is important data, demonstrating the predominance of this species in the São Paulo State region.
Keywords: molecular biology; molecular phylogenetic analysis; paracoccidiodomycosis; Paracoccidioides brasiliensis; Paracoccidioides species complex